Eradicating poverty and promoting prosperity in a changing Asia-Pacific. (Metro Manila, Philippines Asian Development Bank, 2017)
This report is produced under a renewed partnership between United Nations (ESCAP), ADB, and the United Nations Development Programme (UNDP) to support national and regional efforts to implement the 2030 Agenda for Sustainable Development. It explores five megatrends that will determine whether everyone will be able to thrive and fulfill their expectations for a better life in the future: regional economic cooperation and integration; rural urban transitions; demographic changes; ICT access and connectivity; and demand for natural resources.
Keywords: Poverty -- Asia Pacific; Sustainable development; Electronic books